Differences of medically unexplained symptoms among patients of different ages and sexes in the psychological clinic of a general hospital and the influencing factors of MUS: A cross-sectional study - Zhang, Jie; Pan, Yu; Hong, Jiangyue; Guo, Hong; Wang, Mengyu; Liu, Xiaolei; Dong, Yanbin; Wang, Dejun; Liu, Lu; Tan, Shuping; Jiang, Ronghuan (Frontiers in Psychiatry, 2022)
In this cross-sectional study, we analysed differences in sex, age, depression, insomnia, psychological stress, resilience, and perceived social support among patients with MUS who were visiting a psychological clinic of a general hospital for the first time, and we explored the influencing factors of MUS. We evaluated the patients by using various scales (e.g. Patient Health Questionnaire, Insomnia Severity Index; Perceived Stress Scale-10, Connor-Davidson Resilience Scale) to obtain information on sex, age, depression, insomnia, perceived stress, resilience, and perceived social support. We found (1) most patients had moderate and severe physical symptoms and that a high proportion of patients had severe physical symptoms; (2) somatic symptoms were higher in the middle-aged patients than in young patients; (3) before the age of 60 years, somatic symptoms increased with increasing age; (4) more male patients than female patients were young to middle-aged, whereas more female patients were older; (5) women had more severe physical symptoms than did men; and (6) psychological resilience, perceived social support and depression mediated the effects of psychological stress on physical symptoms.